S100A11 Promotes Glioma Cell Proliferation and Predicts Grade-Correlated Unfavorable Prognosis - Wang, Haopeng (Technol Cancer Res Treat, 2021)
The prognosis of glioma is significantly correlated with the pathological grades; however, the correlations between the prognostic biomarkers with pathological grades have not been elucidated. S100A11 is involved in a variety of malignant biological processes of tumor, whereas its biological and clinicopathological features on glioma remain unclear. In this study, the S100A11 expression and clinical information were obtained from the public databases (TCGA, GEPIA2) to analyze its correlations with the pathological grade and the prognosis of glioma patients. We then verified the expression of S100A11 by immunohistochemistry staining. The effects of S100A11 on the proliferation of glioma cells were confirmed by cytological function assays (CCK-8, Flow cytometry, Clone formation assay) in vitro, the role of S100A11 in regulation of glioma growth was determined by xenograft model assay. We observed that S100A11 expression positively correlated with the pathological grades, while negatively correlated with the survival time of patients. In cytological analysis, we found the proliferations of glioma cell lines were significantly inhibited in vitro (P < 0.05) after interfering S100A11 expression via shRNAs. The cell cycle was blocked at G0/G1 stage. The ability of clone formation was significantly decreased, and the tumorigenicity in vivo was weakened (P < 0.05). In summary, S100A11 was over-expressed in gliomas and positively correlated with the pathological grades. Interfering the expression of S100A11 significantly inhibited the proliferation of glioma in vitro and the tumorigenicity in vivo (P < 0.05). In conclusion, S100A11 might be considered as a potential biomarker in glioma.